2018
DOI: 10.1002/ajb2.1066
|View full text |Cite
|
Sign up to set email alerts
|

Organellar phylogenomics inform systematics in the green algal family Hydrodictyaceae (Chlorophyceae) and provide clues to the complex evolutionary history of plastid genomes in the green algal tree of life

Abstract: PREMISE OF THE STUDY:Phylogenomic analyses across the green algae are resolving relationships at the class, order, and family levels and highlighting dynamic patterns of evolution in organellar genomes. Here we present a within-family phylogenomic study to resolve genera and species relationships in the family Hydrodictyaceae (Chlorophyceae), for which poor resolution in previous phylogenetic studies, along with divergent morphological traits, have precluded taxonomic revisions. METHODS:Complete plastome seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 59 publications
0
15
0
Order By: Relevance
“…S1–S5). Most recently this issue received extensive attention in McManus et al (2018), who expanded the taxon sampling in Hydrodictyaceae to 14 species in five genera, but still recovered conflicting relationships between Hydrodictyaceae and Neochloridaceae in different single-gene and concatenated analyses. Expanding the sampling of Neochloridaceae, especially to include the genus Tetraedron , is the next logical step in the effort to resolve this systematic problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S1–S5). Most recently this issue received extensive attention in McManus et al (2018), who expanded the taxon sampling in Hydrodictyaceae to 14 species in five genera, but still recovered conflicting relationships between Hydrodictyaceae and Neochloridaceae in different single-gene and concatenated analyses. Expanding the sampling of Neochloridaceae, especially to include the genus Tetraedron , is the next logical step in the effort to resolve this systematic problem.…”
Section: Discussionmentioning
confidence: 99%
“…Expanding the sampling of Neochloridaceae, especially to include the genus Tetraedron , is the next logical step in the effort to resolve this systematic problem. However, given the varying signal from individual chloroplast and mitochondrial genes reported in McManus et al (2018), it is possible that another confounding factor needs to be considered, such as horizontal gene transfer or insufficient model complexity in analyses. For the scope of our study, positioning of the two families is a minor issue, but the results of McManus et al (2018) exemplify that increased taxon sampling may not always be a sufficient solution to all phylogenetic conflict; adding species helped within Hydrodictyaceae but did nothing to resolve the relationships among closely related families.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staats et al (2011) showed that it is also possible to use genome skimming to analyze DNA that is otherwise too degraded for PCR-based approaches, thus offering the possibility to include rare and extinct species from natural history collections in phylogenetic analyses. Several phylogenomic studies have explored the potential of herbarium specimens of different ages (Staats et al, 2013; Besnard et al, 2014; Aubriot et al, 2018; McManus et al, 2018; Zeng et al, 2018). For example, the entire nuclear genome of a 43-year-old Arabidopsis thaliana (L.) Heynh.…”
Section: Introductionmentioning
confidence: 99%
“…McManus et al. () used organellar phylogenomics to clarify relationships and identify conserved plastome gene order within the chlorophytic algal family Hydrodictyaceae, noting that this conservation contrasts with the dynamic plastome evolution characteristic of Sphaeropleales. Outside of Viridiplantae , Parks et al.…”
Section: Progress In Plant Phylogenomicsmentioning
confidence: 99%